Ensembl 2022. Issue Volume 50:Issue D1(2022) (17th November 2021) - Cunningham, Fiona; Allen, James E; Allen, Jamie; Alvarez-Jarreta, Jorge; Amode, M Ridwan; Armean, Irina M; Austine-Orimoloye, Olanrewaju; Azov, Andrey G; Barnes, If; Bennett, Ruth; Berry, Andrew; Bhai, Jyothish; et al.
Abstract: Ensembl (https://www.ensembl.org ) is unique in its flexible infrastructure for access to genomic data and annotation. It has been designed to efficiently deliver annotation at scale for all eukaryotic life, and it also provides deep comprehensive annotation for key species. Genomes representing a greater diversity of species are increasingly being sequenced. In response, we have focussed our recent efforts on expediting the annotation of new assemblies. Here, we report the release of the greatest annual number of newly annotated genomes in the history of Ensembl via our dedicated Ensembl Rapid Release platform (http://rapid.ensembl.org ). We have also developed a new method to generate comparative analyses at scale for these assemblies and, for the first time, we have annotated non-vertebrate eukaryotes. Meanwhile, we continually improve, extend and update the annotation for our high-value reference vertebrate genomes and report the details here. We have a range of specific software tools for specific tasks, such as the Ensembl Variant Effect Predictor (VEP) and the newly developed interface for the Variant Recoder. All Ensembl data, software and tools are freely available for download and are accessible programmatically.